Knowledge, Attitude and Practice Regarding Body Posture Among UTHM Students - Abdul Rahim, Muhammad Nazmi Ilham; Adisiman, Nur Anis Sofia; Mohd Hafash, Aimun Aisyah; Nawi, Adnin Afifi (Multidisciplinary Applied Research and Innovation, 2025)
Observation found that most UTHM students still do not practice the correct body posture while standing, sitting and sleeping. Therefore, this study was conducted to compare the level of knowledge, attitude and practice regarding body posture between genders among UTHM diploma students.  The significant difference in level of knowledge, attitude and practice of body posture between male and female of UTHM diploma students was also determined. Then, the relationship between knowledge, attitude and practice regarding body posture among UTHM diploma students was identified from the Pearson correlation result. In this paper, a cross-sectional survey among 207 diploma students from UTHM Pagoh was conducted which has seven programme; Diploma in Applied Science (DAU), Mechanical Engineering (DAM), Animation Technology (DAG), Civil Engineering (DAA), Electrical Engineering (DAE), Information Technology (DAT) and Chemical Engineering Technology (DAK) using Google Forms questionnaire. Data collected was analysed using a Statistical Package for Social Science (SPSS) in version 27. The finding showed that female students have a high percentage of level of knowledge and practice regarding body posture, compared with male students. However, male students have a high percentage of level of attitude regarding body posture compared with female students. Based on gender, there were no significant difference in terms of knowledge and attitude of body posture. However, there is exists a significant difference in terms of practice. Moreover, there was a highly significant and moderate positive correlation between knowledge and attitude. However, there was a weak negative correlation between knowledge and practice because the question from the google form questionnaire is more towards to bad habits and weak positive correlation between attitude and practice. The result could be concluded that male and female diploma students have a basic knowledge and attitude of body posture but still have a poor practice of good body posture.  The result of this study could be improved by incorporating pictures alongside the questionnaires. So that respondents could give their responses precisely.